The Alternative Technology of the Grain Storage under the Conditions of the Lack of the Financial Resources of the Agricultural Enterprises (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article stipulates that the vast majority of small and medium-sized grain producers because of the lack of financial resources cannot provide themselves with their own modern silo type granary. It was determined the main tasks which chosen grain storage technology should provide. It was suggested an option of using the so-called Argentinian grain storage technology in plastic bags-sleeves to the low-power domestic enterprises. It was conducted a feasibility study of Argentinian grain storage technology and its benefits for the agricultural enterprises with limited financial resources were defined.
Keywords: logistics, grain, inventory management, Argentinian technology, feasibility study, financial resources